Experimental investigation on the effect of vapor environment on the pattern evolutions during sessile water droplet evaporation at low pressures. (1st February 2023) - Lin, Yuan-Qing; Wu, Chun-Mei; Li, You-Rong
Graphical abstract: Highlights: Pattern evolution path from gear like cells to Bérnard-Marangoni wave is identified. Absorption of ethanol vapor causes solutal-Marangoni flow to weaken buoyancy effect. The critical time for pattern transition is moved forward with the reduced pressure. Surface temperature of water drop in nitrogen is lower than that in ethanol vapor. Abstract: A series of experiments for water droplet evaporation into ethanol and nitrogen vapors at low pressures are carried out to investigate the influence of vapor environment on the evolution of thermal patterns induced by water droplet evaporation. Results show that when the water droplet evaporates in the ethanol vapor, the initial evaporation induces the surface fluid flows from the triple-line to the droplet apex. When the thermal flow loses stabilities, the surface temperature oscillations are shown as types of thermal waves. The transition of thermal patterns from gear-like temperature distribution, shifting multi-cells to the Bénard-Marangoni cell is captured and the wave number increases firstly, and then remains during the pattern evolutions. Reducing the initial pressure leads to an enhancement of the thermocapillary instabilities, which brings the critical time for the pattern transition forward. In the case of nitrogen environment, the transition of thermal patterns from central warmer region to the shifting multi-cells is recorded. The surface temperature in nitrogen environment is lower than that in ethanol vapor. During the whole evaporation process, the tangential temperature gradient and the normal temperature gradient alter as the variation of droplet height, and their relative magnitude determines the internal flow and the evolution of thermal patterns. Moreover, when ethanol vapor is absorbed by the water droplet, the heat of solution is released, and the solutal-Marangoni convection is induced to suppress the buoyancy flow.